The effect of head-to-head competition on behavioural thermoregulation, thermophysiological strain and performance during exercise in the heat - Corbett, J.; White, D. K.; Barwood, M. J.; Wagstaff, C. R. D.; Tipton, M. J.; McMorris, T.; Costello, J. T. (Sports Medicine, 2018)
It has been suggested that pacing is a thermoregulatory behaviour. We investigated the effect of competition on pacing, performance and thermophysiological strain during exercise in the heat and the psychological factors mediating competition effects. Method: Eighteen males (maximum oxygen uptake [VO2max] 3.69 [0.44] L min-1) undertook a preliminary 20-km cool (wet-bulb globe temperature [WBGT] 12 °C) cycling time trial (TT) and three experimental 20-km trials (balanced order): (i) cool TT (CoolSolo); (ii) hot (WBGT 26 °C) TT (HotSolo); (iii) hot head-to-head competition (HotH2H). During TTs, an avatar of the participant`s performance was visible. During HotH2H, participants believed they were competing against another participant, but the competitor`s avatar replicated their own preliminary (cool) TT. Results: TTs (min:sec [SD]) slowed with increased ambient temperature [CoolSolo 35:31 (2:11) versus HotSolo 36:10 (2:26); p = 0.011]. This effect was negated by competition; performances were not different between HotH2H [35:17 (1:52)] and CoolSolo (p = 0.160) and were quicker in HotH2H versus HotSolo (p = 0.001). End-exercise rectal temperature, mean body temperature and physiological strain index were (p < 0.05) higher in HotH2H than either solo condition. Despite faster performance and greater thermophysiological strain, rating of perceived exertion (RPE), thermal comfort and sensation, and perceptual strain index were not different between HotH2H and HotSolo. The difference in end-exercise rectal temperature between HotH2H and HotSolo was related to pre-exercise anticipatory heart rate response (r = 0.608, p = 0.010) and participants` propensity for deliberate risk-taking (B = 0.12, p < 0.001), whereas self-reported resilience predicted change in performance times between HotH2H versus HotSolo (B = - 9.40, p = 0.010). Conclusion: Competition changes the relationship between perceived and actual thermophysiological state, altering behavioural thermoregulation and increasing thermophysiological strain; this could increase heat-illness risk. Psychophysiological and psychological measures may identify susceptible individuals.